The Reliability of Computer-Assisted Three-Dimensional Surgical Simulation of Posterior Osteotomies in Thoracolumbar Kyphosis Secondary to Ankylosing Spondylitis Patients - Yiqi Zhang; Yong Hai; Yuzeng Liu; Xinuo Zhang; Yangpu Zhang; Chaofan Han; Jingwei Liu; Lijin Zhou (Hindawi Limited, 2022)
Objectives. The study was aimed at investigating the reliability of computer-assisted three-dimensional surgical simulation (CA3DSS) of posterior osteotomies in thoracolumbar kyphosis secondary to ankylosing spondylitis (TLKAS) patients. Methods. Eligible TLKAS patients who underwent posterior correction surgery with posterior osteotomies were consecutively included. Simulated posterior osteotomies were performed in Mimics and 3-Matic Medical software. Coronal and sagittal angle and alignment parameters were measured in preoperative full-length X-ray, preoperative original 3D spine (Pre-OS), simulated 3D spine (SS), and postoperative original 3D spine (Post-OS). Reliability was tested by both intraclass correlation coefficients (ICCs) and Bland-Altman analysis. Results. A total of 30 TLKAS patients were included. Excellent consistency of radiological parameters was shown between preoperative X-ray and Pre-OS model. In SS and Post-OS models, excellent reliabilities were shown in global kyphosis (ICC 0.832, 95% CI 0.677-0.916), thoracic kyphosis (ICC 0.773, 95% CI 0.577-0.885), and lumbar lordosis (ICC 0.896, 95% CI 0.794-0.949) and good reliabilities were exhibited in the main curve (ICC 0.680, 95% CI 0.428-0.834) and sagittal vertical axis (ICC 0.619, 95% CI 0.338-0.798). ICCs of correction angle achieved by pedicle subtraction osteotomy (PSO) was 0.754 (95% CI 0.487-0.892), and that of posterior column osteotomies (PCO) was 0.703 (95% CI 0.511-0.829). Bland-Altman analysis also showed good agreement for both Cobb angle and distance measurements in Pre-OS and SS models, and good reliabilities were shown in PCO and PSO in real spine and SS models. Conclusions. CA3DSS can provide an accurate measurement, and it is a reliable and effective method to conduct proper simulation for correction surgery with posterior osteotomies in TLKAS patients. This trial is registered with Chinese Clinical Trial Registry ChiCTR2100053808.